The Post-Digital Enterprise Going Beyond the Hype - Castelli, Gianluigi; Meregalli, Severino; Pennarola, Ferdinando (Cham : Springer International Publishing : Imprint: Springer, 2022)
A new wave of digital technologies has impacted the business world like a tsunami. But after a first phase characterized by hype and unrealistic expectations, there is now a shared need for a better understanding of how to create real and sustainable value by adopting these technologies. This book suggests a pragmatic approach to value creation by embracing the post-digital mindset: a more mature attitude toward digital innovation focused on putting these technologies at work rather than marveling at them. After the illustration of a post-digital manifesto, the book explores all the key topics and tools that are relevant for the decision makers in this context. .
1. Companies and Digital Transformations -- 2. Disruptive as Usual: A Manifesto for the Digital Age -- 3. Redescovering the Fundamentals of Value Creation -- 4. Competences and Capabilities for Digital Value Creation -- 5. Enterprise Renewal and Change Management -- 6. A Tool for the Boardroom: The Devo Lab Hit Radar -- The Hit Radar in Action -- 8. The Legal Side of Digital Technologies: Challenges and New Paradigms -- 9. Enabling the Post-Digital Enterprise.
Keywords: Strategic planning; Leadership; Business information services; Industrial organization; Knowledge management; Business Strategy and Leadership; IT in Business; Organization; Knowledge Management